(untitled) (One Health Journal of Nepal, 2023)
Introduction: Dengue Fever (DF) is a significant public health concern in Nepal, and medical undergraduates play a crucial role in disease prevention and control. This study aimed to assess the knowledge and preventive practices regarding DF among medical undergraduates at KIST Medical College and Teaching Hospital in Nepal. Methods: A descriptive cross-sectional study was conducted among 249 medical undergraduate students, comprising 43.8% males and 56.2% females. Data were collected using a structured questionnaire, assessing participants’ knowledge of Dengue symptoms, transmission, and preventive practices. The data were analyzed using SPSS version 25. Results: Most participants correctly identified Dengue fever as a viral disease transmitted by Aedes mosquitoes (81.9%) and knew that the main cause of transmission is human to mosquito contact (96.4%). However, only 18.1% were aware of all four antigenic subtypes of Dengue prevalent in Nepal. Regarding preventive practices, 98.8% acknowledged that Dengue is preventable, and a significant proportion adopted measures such as usingmosquito bed nets (95.2%) and seeking timely medical attention when symptomatic (95.6%). Conclusions: The study reveals that medical undergraduates at KIST Medical College and Teaching Hospital have good knowledge and positive preventive practices towards Dengue fever. However, knowledge gaps exist, particularly regarding Dengue subtypes and breeding sites. Health education programs are crucial to address these gaps and enhance preventive practices, empowering medical students to become effective advocates for Dengue control in Nepal.Dengue